Paving the Path to Wellness for Okinawan Descendants in Brazil: A Culturally Adapted Lifestyle Medicine Program in Group - Sley Tanigawa Guimaraes; Elizabeth Frates; Julia Pangalangan; Bruna Morais; Fernanda Santos (American Journal of Lifestyle Medicine, 2026)
Noncommunicable chronic diseases (NCDs) are the leading cause of premature death and disability worldwide. Lifestyle medicine group interventions are effective in promoting behavior change and improving health outcomes. This study evaluated the impact of the PAVING THE PATH TO WELLNESS program among Okinawan descendants in São Paulo, Brazil. A longitudinal mixed-methods pilot study was conducted with 16 adults (≥18 years) from the Okinawa Vila Carrão Association. The 8-week group program included weekly sessions addressing purpose, attitude, variety, investigation, movement, stress management, nutrition, sleep, time, relationships, and goal-setting. Pre- and post-intervention surveys assessed health behaviors and literacy. A focus group was conducted at program completion. Quantitative data were analyzed using paired tests, and qualitative data were thematically analyzed. A convergent parallel mixed-methods design integrated both strands to enhance depth and validity.Pre- and post-intervention surveys show that statistically significant changes occurred in stress management ( P = 0.034), nutrition ( P = 0.034), energy ( P = 0.008), experiences ( P = 0.035), and goal-setting ( P = 0.005). The Net Promoter Score was 93.7, indicating high satisfaction. Qualitative findings reinforced these outcomes. Taken together, these findings suggest that the PAVING pilot program was well accepted and effective in promoting health education, lifestyle changes, and reinforcing Okinawan cultural salutogenic resources, supporting its relevance for culturally adapted interventions.